Accelerated Carbonation of Steel Slag Compacts: Development of High-Strength Construction Materials - Quaghebeur, Mieke; Nielsen, Peter; Horckmans, Liesbeth; Van Mechelen, Dirk (Frontiers in Energy Research, 2015)
Mineral carbonation involves the capture and storage of carbon dioxide in carbonate minerals. Mineral carbonation presents opportunities for the recycling of steel slags and other alkaline residues that are currently landfilled. The Carbstone process was initially developed to transform non-hydraulic steel slags [stainless steel (SS) slag and basic oxygen furnace (BOF) slags] in high-quality construction materials. The process makes use of accelerated mineral carbonation by treating different types of steel slags with CO2 at elevated pressure (up to 2 MPa) and temperatures (20–140°C). For SS slags, raising the temperature from 20 to 140°C had a positive effect on the CO2 uptake, strength development, and the environmental properties (i.e., leaching of Cr and Mo) of the carbonated slag compacts. For BOF slags, raising the temperature was not beneficial for the carbonation process. Elevated CO2 pressure and CO2 concentration of the feed gas had a positive effect on the CO2 uptake and strength development for both types of steel slags. In addition, the compaction force had a positive effect on the strength development. The carbonates that are produced in situ during the carbonation reaction act as a binder, cementing the slag particles together. The carbonated compacts (Carbstones) have technical properties that are equivalent to conventional concrete products. An additional advantage is that the carbonated materials sequester 100–150 g CO2/kg slag. The technology was developed on lab scale by the optimization of process parameters with regard to compressive strength development, CO2 uptake, and environmental properties of the carbonated construction materials. The Carbstone technology was validated using (semi-)industrial equipment and process conditions.